Water-spray washing technique as a purification process in the production of biodiesel - Warunee Limmun; Sansanee Sansiribhan (My University, 2020)
In order to meet the standards set for biodiesel after biodiesel production via transesterification, a purification process is necessary. For the purification process, the wet washing method is mostly recommended because it is well-known for its easy application and high efficiency. However, this method requires a large volume of water and takes a long time. Consequently, this study focuses on designing a washing machine that reduces the amount of water used and shortens the application time for the washing method. The spray washing technique, a type of the wet washing method, was used for this study with a focus on the following parameters: the volume of water to crude biodiesel, flow rate, and time. All conditions investigated in the basic standards of biodiesel. The pH value, density, and velocity were considered as the criteria to select the optimum conditions for the washing machine. The results indicated that a volume ratio of 0.8:1 (water:crude biodiesel) and a flow rate of 4 L/min for 0.5 min was the optimum condition of the water washing machine for biodiesel purification that meets the international biodiesel specifications.
Keywords: Biodiesel Production and Applications